Kesulitan bersosialisasi: Melatih kemampuan bersosialisasi mahasiswa terhadap lingkungan Berbahasa Arab - Bulqis, Camelia Malikal (Maliki Interdisciplinary Journal, 2024)
This research aims to describe students' social skills in an Arabic language environment. The research focus includes linguistic and non-linguistic problems faced by students, as well as solutions that can be applied to overcome these social difficulties. This research method uses a qualitative method with data collection techniques through interviews with students, observation of the process of language activities, and documentation. The subjects of this research were 38 students in the PKPBA Arabic language intensive class, UIN Maulana Malik Ibrahim Malang in 2024. The research results show that the main problems faced by students are difficulties in pronunciation (Ashwat 'Arabiyah), vocabulary (Mufrodat), grammar (Qowaid and I'rab), and sentence construction (Tarakib). Apart from that, there are non-linguistic problems such as lack of interest in learning and the influence of teaching staff which influence the learning process. The solution implemented is by practicing pronunciation, increasing the amount of vocabulary memorized and applying it in an effective language environment. Thus, this research emphasizes the importance of the role of teachers in creating a dynamic and conducive learning atmosphere to improve students' Arabic language skills.